Nano additive enhanced salt hydrate phase change materials for thermal energy storage - Kalidasan, B.; Pandey, A. K.; Saidur, R.; Samykano, M.; Tyagi, V. V. (Taylor & Francis, 2023)
Energy storage plays a vital role in sustainable development. Focus on energy storage using phase change materials (PCMs) are of current research hotspot due to high latent heat value. Nevertheless, poor thermal conductivity, supercooling, phase separation, corrosive nature of salt hydrate is of great concern. Distress related to properties of PCM is resolved using nano additives. Major research focus on the dispersion of nano additive with PCM depends on (a) technique of preparing a novel composite PCM; (b) improvement of their thermophysical characteristic; and (c) advanced application for human comfort without polluting the environment. This article presents a critical review of hybridization techniques of metal, carbon and polymer additives on salt hydrate PCMs. To facilitate researchers, the significant variation on thermophysical properties of salt hydrate with nano additives are vitally compared, analysed and critically reviewed. This review article also includes the advanced application of nano additives-based salt hydrate PCMs.